Optimal bank capital - David Miles; Jing Yang; Gilberto Marcheggiano (Bank of England, External Monetary Policy Committee Unit, 2011)
This paper reports estimates of the long-run costs and benefits of banks funding more of their assets with loss-absorbing capital, or equity. Measuring those costs requires careful consideration of a wide range of issues about how shifts in funding affect required rates of return and on how costs are influenced by the tax system; it also requires a clear distinction to be drawn between costs to individual institutions (private costs) and overall economic (or social) costs. Without a calculation of the benefits from having banks use more equity no estimate of costs - however accurate - can tell us what the optimal level of bank capital is. We use empirical evidence on UK banks to assess costs; we use data from shocks to incomes from a wide range of countries over a long period to assess risks to banks and how equity funding (or capital) protects against those risks. We find that the amount of equity capital that is likely to be desirable for banks to use is very much larger than banks have used in recent years and also higher than targets agreed under the Basel III framework.
Keywords: G21; G28; 330; banks; capital regulation; capital structure; cost of equity; leverage; Modigliani-Miller; Bank; Eigenkapital; Fremdkapital; Bankenliquidität; Kapitalstrukturtheorie; Großbritannien